Development of an acoustic guitar tuner and graphical user interface (GUI) using MATLAB - Hasan, Mohammad Mainul; Islam, Saiful (Applied Research and Smart Technology (ARSTech), 2022)
Beautiful music requires precisely tuned instruments. Tuning a guitar is necessary for any guitarist on their first day. This work demonstrates an understanding of the critical characteristics that must be considered while developing an acoustic guitar tuner and the logical process of designing such a tuner. The study aimed to create an algorithm using the Butterworth Filter and Fast Fourier Transform (FFT) capable of adequately analysing the frequency spectrum of a plucked guitar string to determine its fundamental frequency. The developed system compared the detected frequency and the standard frequency of the picked guitar string, which then requested the user on the tuning state of that corresponding string. The error in frequency detection was found to be in the order of 0.02%. The MATLAB App Designer tool created a Graphical User Interface (GUI) that users could use to easily tune guitars using the generated application. The implemented tuner overcame the steep learning curve and high sensitivity of traditional ones.